Favelas cariocas no The Guardian: a cultura vivida e as representações dos impactos das Olimpíadas Rio 2016 - Steffen, Lauren Santos (2020)
The thesis seeks to analyze the tensions between the representations of Rio 2016 Olympic Games impacts in the discourse of the series “Rio Voices: Our Olympic Odyssey” from The Guardian and the lived culture in Rio’s favelas in the context of the mega sports event. The choice of the empirical object was motivated by the space granted to three community journalists from Rocinha, Complexo do Alemão and Complexo da Maré in a global news portal, which totals 160 million monthly browsers. The research aims to contextualize the social, political and economic relations between the 2016 Olympic Games and Rio’s favelas; investigate the journalistic mediations in the series that contribute to the construction of representations of the competition impacts; recognize the meanings mobilized in the journalistic discourse and contrast the representations in the series with the lived culture in Rio’s favelas in the context of the event. The thesis is based on the assumption that the insertion of community journalists may have occurred only in a superficial and limited way, not favoring the active and autonomous participation of these marginalized social groups in order to build more plural and alternative representations. The theoretical-methodological path is developed from a proper analytical protocol based on cultural analysis (WILLIAMS, 1979) and discourse analysis (FOUCAULT, 2012) in order to understand the negotiations of meanings between different cultural spheres. Firstly, we analyze the lived culture by describing the mediations of Rio's favelas in the context of the 2016 Olympic Games and The Guardian journalistic mediations; then we map the meanings negotiated in the series discourse amid power relations and ideological disputes; finally, in an interpretative stage, we contrast the representations of the impacts of the mega sports event in the series with the lived culture of Rio’s favelas in the period in order to verify the potentialities and limitations of the insertion of community voices in a global and hegemonic space. As a result, we identified five discursive formations: a) neglect; b) militarization; c) resistance; d) trivialization of violence and e) stereotyping. The research demonstrates, on the one hand, that the presence of mediations of Rio’s favelas, represented by the community journalists, was a differential in the series, as they put into circulation more plural and alternative representations of the mega sports event, bringing the journalistic discourse closer to the lived culture in the communities. However, it cannot be said that the participation of community journalists took place actively and democratically in the series, as The Guardian had full control of the entire production process, restricting the autonomy of these marginalized voices in a tutored and limited space. Thus, the series involved an asymmetrical power relation in which the local was converted into a product for consumption from the global and hegemonic logics.